2009
DOI: 10.1007/s11130-009-0133-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antiproliferative Activity of Diospyros lotus L. Extract and Isolated Compounds

Abstract: The object of the study was to determine the chemical composition of Diospyros lotus L. extract and their antioxidant and antiproliferative properties. Eight compounds were isolated from D. lotus and identified as gallic acid, methylgallate, ellagic acid, kaempferol, quercetin,myricetin, myricetin 3-O-beta-glucuronide, and myricetin-3-O-alpha-rhamnoside. D. lotus extract tested in different in vitro systems (DPPH, ABTS, FRAP, and Fe2+ chelating activity assay) showed significant antioxidant activity. The poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 29 publications
6
62
2
3
Order By: Relevance
“…As A549 line has been widely used as a model system to study human alveolar carcinoma, cytotoxic profile of flavonoids in these cells was previously characterized with the results very similar to those measured in our work. Indeed, the IC 50 value of 72.2 µM for quercetin is close to the inhibitory constants published by Loizzo et al (26), Tan et al (27)(28)(29), Robaszkiewicz et al (30), and Chan et al (31); and IC 50 values more than 100 µM were previously reported for fisetin (32), hesperetin (33-35), luteolin (32,36), chrysin (35), baicalein (34), daidzein (37), and genistein (38). Based on our results presented in this article, cytotoxic activity profiles of flavonoids were rather similar for both A549 and HCC-44 lung cancer lines, despite the gender difference of initial origin of these cells.…”
Section: Discussionsupporting
confidence: 88%
“…As A549 line has been widely used as a model system to study human alveolar carcinoma, cytotoxic profile of flavonoids in these cells was previously characterized with the results very similar to those measured in our work. Indeed, the IC 50 value of 72.2 µM for quercetin is close to the inhibitory constants published by Loizzo et al (26), Tan et al (27)(28)(29), Robaszkiewicz et al (30), and Chan et al (31); and IC 50 values more than 100 µM were previously reported for fisetin (32), hesperetin (33-35), luteolin (32,36), chrysin (35), baicalein (34), daidzein (37), and genistein (38). Based on our results presented in this article, cytotoxic activity profiles of flavonoids were rather similar for both A549 and HCC-44 lung cancer lines, despite the gender difference of initial origin of these cells.…”
Section: Discussionsupporting
confidence: 88%
“…The data obtained demonstrate a considerable impact of polyphenols on the anticancer activity of the extracts (particularly ethanolic ones). Numerous studies have reported on the antiproliferative activity of flavonoids and tannins [30]. A high cytotoxic activity of According to the data presented in Tables 2 and 4, the antibacterial properties of rose galenic preparations against most of the bacterial strains studied were strongly influenced by flavonoids, except for tinctures where the presence of o-dihydroxyphenols was correlated with antipseudomonal potential.…”
Section: Correlation Between Antiradical Anticancer and Antibacteriamentioning
confidence: 96%
“…Many studies were undertaken to show the influence of phenolic and carotenoid components on the biological activity of plant extracts [24,30]. Likewise, our study was to define the relationship between the biological activity and chemical composition of the extracts.…”
Section: Correlation Between Antiradical Anticancer and Antibacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,7]. 최근의 고욤나무 열매 추출물에서 진정작용, 항당뇨, 항암, 항균효능, 항산화효능, 용혈작용, 신경보호 능이 세포 및 동물실험을 통해 확인되었다 [5,12,18,20,28]. 고욤 잎 추출 물에서는 항알러지 및 항가렴움증 및 항산화, 항염증, 간보호 능에 대한 효능이 보고되었다 [17,22,24].…”
unclassified